2011
DOI: 10.1002/ejoc.201100328
|View full text |Cite
|
Sign up to set email alerts
|

A Protecting‐Group‐Free Route to Chiral BINOL–Phosphoric Acids

Abstract: A two‐step, protecting group‐free route for the synthesis of 3,3′‐disubstituted and 6,6′‐disubstituted chiral BINOL–phosphoric acids has been realized starting from commercially available brominated BINOLs. This synthesis relies on the direct Suzuki coupling of brominated BINOL phosphoric acids. This synthetic strategy is more efficient compared to previous circuitous strategies involving protections and deprotections, and the process is higher yielding relative to the alternative two‐step synthesis involving … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 77 publications
0
8
0
Order By: Relevance
“…Actually, it has been demonstrated that the use of protecting groups is dispensable, and that 3,3′‐substituted BPAs can be prepared either by the bromination–Suzuki cross‐coupling–phosphorylation or by the bromination–phosphorylation–Suzuki coupling sequence. [110] In this way, starting from 3,3′‐dibromo/diiodo BINOL 55 , the number of steps could potentially be reduced to four. The procedure has however been applied just to a limited number of 3,3′‐hindered BPAs (Scheme 23 ).…”
Section: Brønsted Acid Catalystsmentioning
confidence: 99%
“…Actually, it has been demonstrated that the use of protecting groups is dispensable, and that 3,3′‐substituted BPAs can be prepared either by the bromination–Suzuki cross‐coupling–phosphorylation or by the bromination–phosphorylation–Suzuki coupling sequence. [110] In this way, starting from 3,3′‐dibromo/diiodo BINOL 55 , the number of steps could potentially be reduced to four. The procedure has however been applied just to a limited number of 3,3′‐hindered BPAs (Scheme 23 ).…”
Section: Brønsted Acid Catalystsmentioning
confidence: 99%
“…The high reactivity of the BI-DIME ligand enables the coupling to occur under mild reaction conditions with a weak base Na 2 CO 3 , which leads to high enantiopurity of the product even after prolonged heating. Most phosphine ligands require the use of a stronger base to favor the coupling reaction; however, in the meantime, chiral degradation of the isolated products resulted. , Furthermore, the effect of base on the enantiopurity of the product was studied (Table ). It was shown that the enantiopurity of the product 2a remained the same in the presence of K 2 CO 3 and K 3 PO 4 after heating at 70 °C for 48 h (entries 2, 3 and 5, 6) and started to degrade slightly in the presence of NaO- t -Bu (entry 4).…”
Section: Resultsmentioning
confidence: 99%
“…Beller and Köckritz reported the successful Suzuki coupling of partially hydrogenated 3,3′-dibromo-H8-BINOL . However, Chiu and co-workers observed diminished enantiomeric excess (from >99% ee to 94% ee) with a low isolation yield when coupling the enantiomerically pure 3,3′-dibromo-BINOL with phenylboronic acid . Clark et al have reported an elegant synthesis of 3,3′-bis-arylated BINOL derivatives using a one-pot C–H borylation/Suzuki–Miyaura coupling sequence, yet the enantiopurity was preserved only for coupling of the phenyl halides without any substitution .…”
Section: Introductionmentioning
confidence: 99%
“…Considering the existence of BINOL groups in the H-CMPL@HCP-B, we introduced hydrogen phosphate groups by the postsynthesis modification of H-CMPL@HCP-B with phosphoryl chloride and successive acidic quenching to form H-CMPL@HCP-BP 48 (Figure 4a). As a control material, micron-sized HCP-BP (M-HCP-BP) was prepared by the same procedures as H-CMPL@HCP-BP.…”
Section: Acs Macro Lettersmentioning
confidence: 99%